169 Removing Barriers and Facilitating Career Pathways of Hispanic Research Workforce. (April 2022) - de Laurido, Lourdes E. Soto; Frontera, Walter; Ramos, Carlamarie Noboa; Huertas, Aracelis
Abstract : OBJECTIVES/GOALS: The Hispanic-In-Research Capability Endowment Phase (HiREC) Phase I Award supports research academic formation of researchers in Puerto Rico. Since 2011, HiREC provided critical infrastructure resources to develop the Clinical and Translational Research (CTR) workforce. We explored the awardees research career advancements and outcomes. METHODS/STUDY POPULATION: The target population of Phase I Award was young faculty and early-career investigators admitted to the Postdoctoral Master of Science in CTR Program. Eleven awardees were supported from 2011to 2020. A survey was administered via REDCap platform and all awardees were invited by email to participate. Data was collected from 03/15/21 to 05/15/21, including weekly follow-up by email and text messages to increase response rate and 100% responded. Descriptive analyses were performed in SPSS VS 27. The 63.6% was female and 54.6% MD. Most were Hispanic faculty and investigators (36.4%) or were at the clinical practice (36.4%). The 45.5% were affiliated to an academic institution or healthcare entrepreneur RESULTS/ANTICIPATED RESULTS: Awardees top career goals were: combine research & teaching-faculty (36.4%), clinical practice (36.4%) and Principal Investigator (PI) in a research institution (36.4%). The 81.8% of awardees achieved those goals and 18.2% are working-on it. A total of 57 grants were submitted (M=10, SD=10.9) and 42.1% funded. Most awardees submitted grants as PI (45.6%) or Co-I (42.1%). Additional outcomes were: 49 peer-reviewed publications, 67 posters and 21 oral presentations. Awardees expressed that this award: provided resources and necessary tools to support the research career pathway; served to develop essential research capabilities, knowledge and skills; and was a unique opportunity to protected-time for research. DISCUSSION/SIGNIFICANCE: HiREC provided resources, opportunities, and tools to remove barriers and facilitate career pathways of Hispanic investigators. Awardees achieved their career goals, their grant success rate was over 40%; received R-grants awards and published over 45 articles. This award model developed promising Hispanic researchers.